2007
DOI: 10.2190/ic.27.1.g
|View full text |Cite
|
Sign up to set email alerts
|

The Archaic Belief in Dream Visitations as it Relates to “Seeing Ghosts,” “Meeting the Lord,” as Well as “Encountering Extraterrestrials”

Abstract: The current study was designed to determine whether archaic belief in the external origins of dream visitations survives and whether it accounts for the paranormal experience of seeing ghosts, the fundamentalist religious experience of “meeting the Lord,” and the sci-fi experience of encountering extraterrestrials. Over half of the study's 163 subjects professed belief that the deceased can actually visit us in dreams; nearly half professed belief that God can actually visit us in dreams; and one-fifth profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Section A: Studies of (Isolated) Sleep Paralysis Ghost/(evil) spirit/witch/soul-related 356 (56%) of 635 ps answered 'yes' or 'perhaps yes' to a relationship between Kanashibari and spirits (Fukuda et al, 1987) 39 (93%) of 42 ps believed that their SP was the 'soul scared from the body', and 38 (91%) of 42 ps believed that their SP was due to a fatal spirit attack (Hinton et al, 2005) 43 (48%) and 20 (22%) of 89 ps from the general population in Egypt believed that their SP was caused by Jinn or Shaitan, respectively (Jalal et al, 2014) 5 (11%) of 44 students in Cairo believed that their SP was caused by the Jinn (Jalal et al, 2014) 26 (38%) of 68 ps reported that their SP was possibly due to pandafeche (Jalal et al, 2015) 4 (6%) of ps with SP called it the 'pandafeche attack' (Jalal, Romanelli, & Hinton, 2021) 10 (17%) of 59 ps believed that their SP was possibly caused by the Karabasan (Jalal, Sevde Eskici, et al, 2021) 5 (29.4) of 17 ps thought that their SP was caused by a ghost (McNally & Clancy, 2005) 43 (39%) of 110 ps believed that their ISP had supernatural causation (Ohaeri et al, 2004) 2 (5.6%) of 36 ps believed that their ISP was caused by a ghost/evil spirit (Ramsawh et al, 2008) (Cheyne & Girard, 2009) SP ps (M = .19, SD = .39) scored higher on OBEs than controls (M = .08, SD = .27), p < .01 (Spanos et al, 1995) Unspecified Ghost/(evil) spirit/witch/soul-related 42 (60%) of 70 ps had dreams about being chased by a ghost (Hinton et al, 2020) Dream visitations 62 (62%) of 100 reported visitations in their dreams (Hinton et al, 2013) 94 (59%) of 160 ps believed that the deceased can visit us in dream (Kunzendorf et al, 2007) Section G: Studies of Exploding Head Syndrome (EHS)…”
Section: Associated Opepb Study Results Amentioning
confidence: 99%
See 1 more Smart Citation
“…Section A: Studies of (Isolated) Sleep Paralysis Ghost/(evil) spirit/witch/soul-related 356 (56%) of 635 ps answered 'yes' or 'perhaps yes' to a relationship between Kanashibari and spirits (Fukuda et al, 1987) 39 (93%) of 42 ps believed that their SP was the 'soul scared from the body', and 38 (91%) of 42 ps believed that their SP was due to a fatal spirit attack (Hinton et al, 2005) 43 (48%) and 20 (22%) of 89 ps from the general population in Egypt believed that their SP was caused by Jinn or Shaitan, respectively (Jalal et al, 2014) 5 (11%) of 44 students in Cairo believed that their SP was caused by the Jinn (Jalal et al, 2014) 26 (38%) of 68 ps reported that their SP was possibly due to pandafeche (Jalal et al, 2015) 4 (6%) of ps with SP called it the 'pandafeche attack' (Jalal, Romanelli, & Hinton, 2021) 10 (17%) of 59 ps believed that their SP was possibly caused by the Karabasan (Jalal, Sevde Eskici, et al, 2021) 5 (29.4) of 17 ps thought that their SP was caused by a ghost (McNally & Clancy, 2005) 43 (39%) of 110 ps believed that their ISP had supernatural causation (Ohaeri et al, 2004) 2 (5.6%) of 36 ps believed that their ISP was caused by a ghost/evil spirit (Ramsawh et al, 2008) (Cheyne & Girard, 2009) SP ps (M = .19, SD = .39) scored higher on OBEs than controls (M = .08, SD = .27), p < .01 (Spanos et al, 1995) Unspecified Ghost/(evil) spirit/witch/soul-related 42 (60%) of 70 ps had dreams about being chased by a ghost (Hinton et al, 2020) Dream visitations 62 (62%) of 100 reported visitations in their dreams (Hinton et al, 2013) 94 (59%) of 160 ps believed that the deceased can visit us in dream (Kunzendorf et al, 2007) Section G: Studies of Exploding Head Syndrome (EHS)…”
Section: Associated Opepb Study Results Amentioning
confidence: 99%
“…Frequency analysis reporting on the associations between dreams and OPEPB (Table 2) was identified in three papers. Specifically, two studies found that most of their participants (Cambodian refugees and psychology students; 62% and 59% respectively) believed that they were being visited by a deceased relative in their dreams (Hinton et al, 2013; Kunzendorf et al, 2007). Another study found that the majority of participants (60%) reported being visited by a ghost (Hinton et al, 2020).…”
Section: Resultsmentioning
confidence: 99%